2004
DOI: 10.1038/sj.onc.1207415
|View full text |Cite
|
Sign up to set email alerts
|

SUMO: a regulator of gene expression and genome integrity

Abstract: Post-translational modification with the ubiquitin-like SUMO protein is involved in the regulation of many cellular key processes. The SUMO system modulates signal transduction pathways, including cytokine, Wnt, growth factor and steroid hormone signalling. SUMO frequently restrains the activity of downstream transcription factors in these pathways presumably by facilitating the recruitment of corepressors or mediating the assembly of repressor complexes. Additionally, evidence is accumulating that SUMO contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
265
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(274 citation statements)
references
References 124 publications
(122 reference statements)
8
265
0
1
Order By: Relevance
“…Sumoylation of transcription factors and co-factors inhibits transcription in most cases and activates transcription in others (Seeler and Dejean, 2003;Johnson, 2004;Muller et al, 2004). We found that sumoylation of Ets-1 leads to reduced transcription, with the sumoylation defective mutants having a greater capacity to activate transcription than Ets-1.…”
Section: Discussionmentioning
confidence: 74%
“…Sumoylation of transcription factors and co-factors inhibits transcription in most cases and activates transcription in others (Seeler and Dejean, 2003;Johnson, 2004;Muller et al, 2004). We found that sumoylation of Ets-1 leads to reduced transcription, with the sumoylation defective mutants having a greater capacity to activate transcription than Ets-1.…”
Section: Discussionmentioning
confidence: 74%
“…As ubiquitination occurs in the C-terminal region of pRb, which is heavily modified by other post-translational modifications (Figure 1), it is possible that interplay exists between ubiquitination and other modifications such as phosphorylation, acetylation and methylation. SUMO (small ubiquitin-related modifier) is a reversible post-translational modification, and many of its protein targets include transcriptional regulators (Muller et al, 2001(Muller et al, , 2004Wilkinson and Henley, 2010). pRb is SUMOylated in the B domain of the pocket region on K720 (Ledl et al, 2005) (Figure 1), within a cluster of lysine residues that are essential for the interaction with LXCXE motif-containing proteins (Chan et al, 2001b).…”
Section: Other Prb Post-translational Modificationsmentioning
confidence: 99%
“…In fact, the same lysine residues are acetylated by histone acetyl transferases (HATs) which result in p53 stabilization and activation. [43][44][45] Finally, there are data that neddylation, 44 methylation, 46 and sumoylation (reviewed in Muller et al 47 ) of the CTD can regulate p53 functions.…”
Section: The P53 C-terminal Dna-binding Domainmentioning
confidence: 99%